2003
DOI: 10.1007/bf02442581
|View full text |Cite
|
Sign up to set email alerts
|

Probing the stability of the disulfide radical intermediate of thioredoxin using direct electrochemistry

Abstract: SummaryThioredoxin, a redox active disulfide protein, has been specifically immobilized at a modified gold electrode. The thioredoxin is uniquely oriented relative to the electrode surface via a histidine tag thereby enabling the redox mechanism of protein to be examined. When scanning the applied potential in the negative direction (cathodic), two one-electron reduction waves can be observed. The first of these redox waves occurs at -90 mV and is electrochemically reversible at all scan rates whereas the seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 18 publications
4
18
0
Order By: Relevance
“…Control experiments performed after Cys alkylation showed that no electrochemical response occurs for the S-alkylated cofilin-2. Moreover, the E° values are similar to those obtained for disulfide reduction in other proteins [ 32 , 33 ]. Therefore, the observed electrochemical response can be confidently assigned to the formation of an intramolecular disulfide bridge between Cys39 and Cys80.…”
Section: Resultssupporting
confidence: 82%
“…Control experiments performed after Cys alkylation showed that no electrochemical response occurs for the S-alkylated cofilin-2. Moreover, the E° values are similar to those obtained for disulfide reduction in other proteins [ 32 , 33 ]. Therefore, the observed electrochemical response can be confidently assigned to the formation of an intramolecular disulfide bridge between Cys39 and Cys80.…”
Section: Resultssupporting
confidence: 82%
“…Such studies yielded a range of E m values between -261.5 and -265 mV for Ec Trx, and -210 mV for both m and f spinach thioredoxins. 91-93 These E m values measured by direct protein electrochemistry are comparable to those calculated from K eq measurements as described above. More importantly, protein-film voltammetry revealed a fast electrochemical connection between a sub-monolayer of the protein being analyzed and the electrode, which has allowed the direct observation of the reversible 2e − /2H + redox couple of thioredoxins.…”
Section: Redox Potential Of the Active Thiols In The Cxxc Motifsupporting
confidence: 81%
“…Previous electrochemical investigations of plant‐type and Escherichia coli Trx disulfides did not yield reversible 2 e − voltammetry: instead quasireversible 1 e − cyclic voltammetry for the disulfide/disulfide radical potential and an second irreversible feature (corresponding to the reduction of the radical intermediate) was observed 3. 4 Martin and co‐workers have developed a modified gold electrode to investigate His‐tag‐labeled E. coli Trx; they too were unable to directly observe a reversible 2 e − potential5 and could only establish reversible voltammetry for the 1 e − disulfide/disulfide radical couple 5. 6 As the biologically significant reaction for thioredoxins involves cooperative 2e − chemistry,7, 8 we have examined a series of members of the Trx superfamily to observe a reversible 2 e − /2 H + reaction by using PFV.…”
Section: Measured Midpoint Potentials and Peak Widths Of Trx Proteinsmentioning
confidence: 99%